\(B=\left|3x-1\right|+12x-1\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 1 2019

Ta có : \(\left|3x-1\right|=3x-1\) với \(3x-1\ge0\Leftrightarrow3x\ge1\Leftrightarrow x\ge\frac{1}{3}\)

\(\left|3x-1\right|=-3x+1\)với \(3x-1< 0\Leftrightarrow3x< 1\Leftrightarrow x< \frac{1}{3}\)

Suy ra : Với : \(x\ge\frac{1}{3}\)thì \(B=3x-1+12x-1=15x-2\)

Với : \(x< \frac{1}{3}\)thì \(B=-3x+1+12x-1=9x\)

22 tháng 1 2019

\(+,x\ge\frac{1}{3}\Rightarrow B=|3x-1|+12x-1=3x-1+12x-1=15x-2\)

\(+,x< \frac{1}{3}\Rightarrow B=|3x-1|+12x-1=1-3x+12x-1=9x\)

12 tháng 6 2018

\(a,\left(3x+5\right)^2+\left(3x-5\right)^2-\left(3x+2\right)\left(3x-2\right)=9x^2+30x+25+9x^2-30x+25-9x^2+4=9x^2+54\)
\(b,BT=2x\left(4x^2-4x+1\right)-3x\left(x^2-9\right)-4x\left(x^2+2x+1\right)=8x^3-8x^2+2x-3x^3+27x-4x^3-8x^2-4x=x^3-16x^2+25x\)
\(c,BT=\left(x+y-z\right)^2-2\left(x+y-z\right)\left(x+y\right)+\left(x+y\right)^2=\left(x+y-z-x-y\right)^2=z^2\)

5 tháng 8 2020

a)

\(A=\left(x+3\right)\left(x^2-3x+9\right)-\left(54+x^3\right)\)

\(=x^3-3x^2+9x+3x^2-9x+27-54-x^3\)

\(=-27\)

or

\(A=x^3+27-54-x^3=-27\)

b)

\(B=\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)

\(=8x^3+y^3-8x^3+y^3=2y^3\)

c)

\(C=\left(2x+1\right)^2+\left(1-3x\right)^2+2\left(2x+1\right)\left(3x-1\right)\)

\(=\left(2x+1+3x-1\right)^2=\left(5x\right)^2=25x^2\)

d)

\(D=\left(x-2\right)\left(x^2+2x+4\right)-\left(x+1\right)^3+3\left(x-1\right)\left(x+1\right)\)

\(=x^3-8-\left(x-1\right)^3+3\left(x-1\right)\left(x+1\right)\)

\(=6x^2-3x-10\)

4 tháng 11 2016

a ) \(A=\frac{ax^2\left(a-x\right)-a^2x\left(x-a\right)}{3a^2-3x^2}=\frac{ax\left(a-x\right)\left(a+x\right)}{3\left(a-x\right)\left(a+x\right)}=\frac{ax}{3}\)

Thay \(a=\frac{1}{2};x=-3\), ta có :

\(A=\frac{\frac{1}{2}.-3}{3}=-\frac{1}{2}\)

b ) \(B=\frac{\left(ab+bc+cd+da\right)abcd}{\left(c+d\right)\left(a+b\right)+\left(b-c\right)\left(a-d\right)}=\frac{\left[\left(ab+ad\right)+\left(bc+cd\right)\right]abcd}{ca+cb+da+db+ba-bd-ca+cd}\)

\(=\frac{\left[a\left(b+d\right)+c\left(b+d\right)\right]abcd}{ba+da+cb+cd}=\frac{\left(b+d\right)\left(a+c\right)abcd}{\left(b+d\right)\left(a+c\right)}=abcd\)

Thay \(a=-3;b=-4;c=2;d=3\), ta có :

\(B=\left(-3\right).\left(-4\right).2.3=72\)

 

4 tháng 1 2019

ghi hết đầu bài ra

4 tháng 1 2019

ghi rồi